Implementation of Islamic Nursing Care in Improving Patient Satisfaction - Musviro, Musviro; Munawir, Al; Zulkarnain, Elfian (Health Notions, 2017)
Hospital must have a superiority in order to survive and compete with other hospitals which have patients satisfaction oriented. One of the factors that influence the patientsâ satisfaction is nursing care. Nursing care must relevant with Islamic rule that it was basic for nurses in practicing nursing care plan. The purpose of this research was to analyze the influence of Islamic nursing care phases of orientation, working, and termination on patientsâ satisfaction level in Lumajang Islamic hospital. The respondent 92 people were taken by proportionate stratified random sampling. The instrument used was check list of Islamic nursing care phases of orientation, working, termination, and questionnaire of patientsâ satisfaction. The result of ordinal regression test showed that there were significant influence in all phases of Islamic nursing care of orientation, working, and termination on patientsâ satisfaction level in Lumajang Islamic hospital where p<0.05 and wald > 3.84/df (in orientation p = 0.000 and wald 14. 274; working p = 0.000 and wald 12.230; termination p = 0.000 and wald 20.850). Islamic nursing care which most significant was termination phase. Islamic nursing care was significantly influence on patientsâ satisfaction; therefore it could be used as guidelines for nurses on practicing nursing care plans.